Bottlenecks in the Transformation of Eastern Europe - Vojtech Cepl (Washington University Journal of Law & Policy, 2000)
We are approaching the tenth anniversary of the 1989 revolutions in Central and Eastern Europe, and so you might ask: Why is he still talking about the transformation in Eastern Europe? The reason is simple: We are still in the midst of the transformation and, in some respects, the pendulum is swinging back. In many cases, what was done was accomplished imperfectly because the needs and the nature of the transformation were poorly understood. While political institutions can be reformed relatively quickly (after all, we have models to follow), the reform effort did not transform the political culture. As a result, there is now a tendency to feel nostalgic for the old days, reflected in a renewed popularity of the former communist parties. The economic systems were reformed to a certain degree, however, as I shall explain below, the inherent, but more subtle, obstacles in transforming a backward economy are now revealing themselves. Moreover, although the legal system underwent significant modifications, it still does not function properly to meet the needs of, for example, a market economy.
Keywords: Eastern Europe; Political reform; Economic reform; Legal reform